MPS 18-02 ENDOTHELIN-1 OVEREXPRESSION PRESERVES ENDOTHELIAL FUNCTION IN MICE WITH VASCULAR SMOOTH MUSCLE CELL-SPECIFIC DELETION OF PPAR-GAMMA. (September 2016) - Ouerd, Sofiane; Idris-Khodja, Noureddine; Trindade, Michelle; Gornitsky, Jordan; Rehman, Asia; Offermanns, Stefan; Gonzalez, Frank; Barhoumi, Tlili; Paradis, Pierre; Schiffrin, Ernesto
Abstract : Objective: Peroxisome proliferator-activated receptor γ (PPARγ) agonists reduce blood pressure (BP) and vascular injury in hypertensive rodents. Pparγ inactivation in vascular smooth muscle cells (VSMC) using a tamoxifen inducible Cre-Lox system enhanced angiotensin II-induced vascular damage. Transgenic mice overexpressing endothelin (ET)-1 in the endothelium (eET-1) exhibit endothelial dysfunction, increased oxidative stress and inflammation. We hypothesized that inactivation of the Ppar gene in VSMC (sm Pparγ −/− ) will exaggerate ET-1-induced vascular damage. Design and Method: Eleven week-old male control, eET-1, sm Pparγ −/− and eET-1/sm Pparγ −/− mice were treated with tamoxifen (1 mg/kg/day,  s.c.) for 5 days and sacrificed 4 weeks later. BP was measured by telemetry. Endothelial function and vascular remodeling using pressurized myography, reactive oxygen species (ROS) production by dihydroethidium staining, monocyte/macrophage infiltration by immunofluorescence and mRNA expression by reverse transcription-quantitative PCR were assessed in mesenteric arteries (MA) or perivascular fat (PVAT). Spleen T cell and monocyte profiles were assessed by flow cytometry. Results: Systolic BP was 20 mmHg higher in eET-1 and unaffected by Pparγ inactivation. MA vasorelaxation to acetylcholine was impaired 37% only in sm Pparγ −/− . Likewise, ET-1-induced contractions were enhanced only in sm Pparγ −/− . ROS levels were increased 1.7-fold in sm Pparγ −/− and 2.5-fold in eET-1/smPparγ −/− . Monocyte/macrophage infiltration in PVAT was 2-fold higher in eET-1 and sm Pparγ −/−, which was further increased 2-fold in eET-1/sm Pparγ −/− . The percentage of CD11b + cells was increased 2.3-fold in smPparγ −/− and further increased 1.5-fold in eET-1/smPparγ −/− . The percentage of Ly-6C hi monocytes was increased ∼1.8-fold in eET-1 and smPparγ −/− but not eET-1/sm Pparγ −/− . The percentage of T regulatory cells was increased 1.5-fold in sm Pparγ −/− and decreased by 26% in eET-1, which was further decreased by 38% in eET-1/sm Pparγ −/− . Conclusions: These results suggest that increased ET-1 paradoxically preserves endothelial function in mice with inactivated VSMC P parγ despite enhanced oxidative stress. Flow cytometry data indicate that infiltrating monocyte/macrophages in these mice might be anti-inflammatory.